Ecological solidarities : mobilizing faith and justice for an entangled world - Hughes, Krista E. (Krista Elizabeth), 1971-; Martin, Dhawn, 1970-; Padilla, Elaine (World Christianity (University Park, Pa.), 2019)
"Employs academic, activist, and artistic perspectives to explore ecologies of interdependence as a frame for religious, theological, and philosophical analysis and practice"--